Proceso atención de enfermería en lactante mayor con convulsiones febril más gastroenteritis. - Sudario Valero, Damaris Tamara (2021)
The clinical case to study was chosen at the Martin Icaza General Hospital, it belongs to a female patient, an infant older than 2 years of age, attended the health home with a referral from the Pimocha health center for presenting ± 2 hours of evolution after suffering a febrile seizure, accompanied by threw up, hyperthermia, liquid stools, abdominal pain, loss of appetite, tachycardia, diaphoresis, general malaise, asthenia, dehydrated mucous membranes, without the presence of alterations in the respiratory system, it is evaluated through physical examination, Laboratory tests set to the theoretical model of Virginia Henderson's 14 needs, she is hospitalized due to dehydration, being a risk at her age, initially she has continuous venous access, she changes her diet, the thermal rise is monitored with the application of physical means and control of water balance, daily cleaning, continuity of pharmacological treatment and nursing care process proposed or.